PERANCANGAN SISTEM INFORMASI PELAYANAN JASA LAUNDRY BERBASIS WEB PADA XAVIA LAUNDRY MENGGUNAKAN METODE WATERFALL - Muhammad Anis; Erlangga Triantara Putra (PT Triputra Sejahtera Prima, 2026)
Xavia Laundry still records transactions manually, which leads to inefficiencies, recording errors, reporting delays, and a lack of information integration. This study aims to design and develop a web-based Laundry Service Information System using the Waterfall method. Data collection was conducted through observation, interviews, and document review, followed by requirements analysis, system design using UML, implementation using PHP, MySQL, JavaScript, and Bootstrap, and testing using the black-box method. The resulting system is capable of managing customer data, recording service transactions, automatically calculating costs, monitoring the status of laundry processing in real time, and generating accurate transaction and operational reports. Black-box testing was performed on 15 scenarios covering login functions, laundry status checks, transaction management, order cancellations, operational data management, admin and user roles, report printing, theme changes, and logout. All test scenarios were successfully executed according to specifications with a 100% success rate. The research results show that the system is capable of reducing recording errors, speeding up service processes, and improving information transparency. However, the system is still running in a local environment (localhost) and supports only one user role; therefore, further development should include an online implementation, online booking features, digital payment integration, and automatic notifications via WhatsApp, as well as information transparency.